PENGARUH FREE CASH FLOW, NON DEBT TAX SHIELD TERHADAP KEBIJAKAN HUTANG - ANGGUN PUTRI ROMADHINA (Universitas Pamulang, 2018)
This study aims to empirically test the effect of Free Cash Flow and Non Debt Tax Shield on Debt Policy at Property and Real Estate companies listed on Indonesia Stock Exchange. The period used is 5 (five) years 2012 until 2016. This research uses Debt Policy as dependent variable, Free Cash Flow and Non Debt Tax Shield as independent variable. Population in this research is all Property and Real Estate Company listed in Indonesia Stock Exchange that is amounted to 61 company. This research uses purposive sampling technique and get as many as 11 (eleven) companies that meet the criteria of data sample selection. The results of this study indicate that partially Free Cash Flow variables affect the debt policy. Non Debt Tax Shield variable has an effect on debt policy. Meanwhile, simultaneously shows that the variables of Free Cash Flow and Non Debt Tax Shield effect on debt policy.